Álmodozás és valóság. Gondolatok az olvasási szokásainkról Stephenie Meyer könyve nyomán - KUN, Mária (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2015)
Daydream and reality – reflections about our ways of reading conform a book of Stephenie Meyer. When we speak about anniversaries, we think about the years, decades. We are con- fronted with all that has changed, and what is promoted as eternal human. In the 21st century both adults and children are confronted almost in a time competition to the questions of immortality and eternal life. They/We are looking for answers, the question is where are our readers in this line? What we read and what they read, if our youth read anyway? The generations to come often live with criticism, and it is difficult to discover if other thoughts are involved, but there are everlasting themes to which all generations are looking for answers, and we have to discover which chan- nels are useful to have success. To Géza Hegedűs opinion that reading man matters who is constantly in an in- timate relation with a book. In addition, it is important to get the recognition: the love of God so emanates to us, that God incarnated in his Son, so you can see and feel love. Love Him because He loved us first, which overcomes the fear and paves the way for immortality.